KEBERADAAN SILEK GALOMBANG DI NAGARI LANSEK KADOKKECAMATAN RAO SELATAN KABUPATEN PASAMAN - Ananda, Meliza; Asriati , Afifah (Avant-garde: Jurnal Ilmiah Pendidikan Seni Pertunjukan, 2025)
This research discusses the existence of Silek Galombang in Nagari Lansek Kadok, Rao Selatan District, Pasaman Regency, which is a traditional Minangkabau art rooted in martial arts and passed down through generations. Silek Galombang in this village has the main function of being part of the welcoming ceremony for the Rajo and village head during Idul Fitri, and can also be performed at wedding celebrations provided there is a kinship bond with the customary figure. This study uses descriptive qualitative methods through observation, interviews, and documentation, with the researcher as the main instrument assisted by recording devices, cameras, and field notes. This research discusses the existence of Silek Galombang in Nagari Lansek Kadok, Rao Selatan District, Pasaman Regency, which is a traditional Minangkabau art rooted in martial arts and passed down through generations. Silek Galombang in this village has the main function of being part of the welcoming ceremony for the Rajo and village head during Idul Fitri, and can also be performed at wedding celebrations provided there is a kinship bond with the customary figure. This study uses descriptive qualitative methods through observation, interviews, and documentation, with the researcher as the main instrument assisted by recording devices, cameras, and field notes.